Gentianose: Purification and structural determination of an unknown oligosaccharide in grape seeds. (15th May 2021) - Imperio, Daniela; Bordiga, Matteo; Passos, Claudia P.; Silva, Soraia P.; Coimbra, Manuel A.; Travaglia, Fabiano; Arlorio, Marco; Coïsson, Jean Daniel; Panza, Luigi
Highlights: Low molecular weight oligosaccharides were found into grape seeds aqueous extract. Oligosaccharides were separated on the molecular weight base through gel filtration. Oligosaccharides were identified by NMR Spectroscopy and GC Mass Spectrometry. Gentianose was firstly discovered in grape seeds. Abstract: Grape seeds are among the main constituents of grape pomace, ranging between 20% and 30% of the wet matrix; however, their oligosaccharide composition has not been studied. This paper describes the purification and the identification of low molecular weight oligosaccharides contained in an EtOH/water extract of grape seeds. A sequential two-step purification by size exclusion chromatography was carried out to fractionate compounds according to molecular weights. Chemical characterization of the combined fractions was performed by Magnetic Resonance Spectroscopy and Gas Chromatography-Mass Spectrometry analyses. The separation process gave two fractions abundant in sucrose and glucose. A third fraction containing trisaccharides was acetylated allowing the purification of the main trisaccharide. The structure elucidation of the acetylated product made it possible to identify gentianose, a predominant carbohydrate reserve found in the storage roots of perennial Gentiana lutea . Grape seeds are wine industry by-products and the obtained results suggest the importance of their recovery.